Konstruksi Primer Untuk Mendeteksi Mutasi Gen rpoB Mycobacterium tuberculosis Dengan Metode Amplification Refractory Mutation System (ARMS)-PCR - Arif Sardi (Elkawnie: Journal of Islamic Science and Technology, 2015)
Quickly recognize drug resistance in Mycobacterium tuberculosis is very important for the efficiency of the treatment and control of the disease. More than 95% of RIF resistance occurs due to point mutations in the 81-bp region of the rpoB gene M. tuberculosis. Generally, the mutation occurs at codon 531, 526 and 516. One of method to detect the mutation is using ARMS-PCR. In order to apply the ARMS-PCR technique to detection of mutations needed a special and specific primer. Primer design process using computer software "Primer Designer" and the specificity was confirmed with "Bioedit". Accuracy and ability of all these primers to detecting mutation in rpoB gene M. tuberculosis tested using ARMS-PCR method. PCR amplification results were then analyzed using the techniques of electrophoresis on agarose 1.5%. Electrophoresis results showed two bands produced from the amplification with the template H37RV (wild type). Both bands are expected to be in a position 238 bp and 484 bp, in the other hand the result amplification with the template from mutant strains produce one band with sized 484 bp. From these data it is known that ARMS-PCR reactions are performed can be used to detect mutations in the rpoB gene of M. Tuberculosis.